Factores que influyen en la intención de compra de alimentos orgánicos en los consumidores millennials de Lima Metropolitana - Villanueva Rodríguez, Noelia (2022)
This document seeks to determine how factors influence the intention to purchase organic food in millennial consumers in Metropolitan Lima. The type of research is applied, since it focuses on highlighting a benefit to society. In addition, the descriptive study was taken, because two variables will be nalyzed: Factors (independent variable) and purchase intention (dependent variable). 384 surveys were conducted to consumers and connoisseurs of organic food ranging between 28 and 40 years of socioeconomic level A and B1. A statistically significant relationship was determined between the attitude and intention to purchase organic food in millennial consumers in Metropolitan Lima; characterized by a Spearman correlation coefficient of 0.924. Likewise, subjective norms and purchase intention also have a statistically significant relationship, with a coefficient value of 0.864; between perceived control and purchase intention with a value of 0.969; between awareness and purchase intention with a Spearman correlation coefficient value of 0.958 and, finally, between the behavior of the potential customer and purchase intention with a coefficient value of 0.969.